2021
DOI: 10.1007/s10875-021-01120-5
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and Reference Ranges of Serum Immunoglobulins in Middle-Aged and Elderly Individuals: a Population-Based Study

Abstract: Purpose In clinical practice, currently one reference range for serum immunoglobulin (Ig) A, G, and M is applied to all adults, although various factors may influence Ig serum levels. Population-based data on determinants of IgA, IgG, and IgM and recommendations for subgroup specific reference ranges are lacking. We aimed to provide an overview of determinants of IgA, IgG, and IgM in community-dwelling middle-aged and elderly individuals and explore determinants that influence Ig reference ranges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 55 publications
5
17
0
Order By: Relevance
“…In human plasma (i.e., blood from which cells have been depleted) three dominant classes of immunoglobulins are present, namely IgG, IgA and IgM. Their concentration levels differ per individual but are generally highest for IgG 8.3-11.2 g/L, and somewhat lower for IgA 1.6-2.8 g/L and IgM 0.6-1.2 g/L ( 2 ). For human IgG, four sub-classes can be distinguished, IgG1, IgG2, IgG3 and IgG4, and for human IgA two sub-classes co-exist: IgA1 and IgA2.…”
Section: Introductionmentioning
confidence: 99%
“…In human plasma (i.e., blood from which cells have been depleted) three dominant classes of immunoglobulins are present, namely IgG, IgA and IgM. Their concentration levels differ per individual but are generally highest for IgG 8.3-11.2 g/L, and somewhat lower for IgA 1.6-2.8 g/L and IgM 0.6-1.2 g/L ( 2 ). For human IgG, four sub-classes can be distinguished, IgG1, IgG2, IgG3 and IgG4, and for human IgA two sub-classes co-exist: IgA1 and IgA2.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is little evidence regarding whether immunoglobulin levels are related to depression in older adults. In previous studies, immunoglobulin A levels were lower in Caucasians and showed no significant differences across other ethnicities [ 12 14 ]. In addition, data on the associations between immunoglobulins and depression in Asian populations are scarce, especially for Chinese older adults.…”
Section: Introductionmentioning
confidence: 90%
“…Researchers [ 12 , 13 ] have realized that immunoglobulin A levels were closely associated with age in older adults. Immunoglobulin A levels were found to increase with age in a study involving 8768 participants with a median age of 62 years [ 14 ]. However, there is little evidence regarding whether immunoglobulin levels are related to depression in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study of 39 healthy volunteers, older compared to younger individuals had higher Ig levels in the bronchoalveolar fluid and lower predicted lung function values, although the latter did not reach statistical significance ( 10 ). Recently, we have shown age-related increases of serum IgA and IgG in our general population cohort of middle-aged and older individuals ( 11 ). It is unclear whether an association exists of serum Igs with pneumonia or impaired lung function in this older population.…”
Section: Introductionmentioning
confidence: 92%